Prairie Print Makers - Coutts Memorial Museum (Symphony in the Flint Hills, 2014)
The Prairie Print Makers Society was organized on December 28, 1930 at the studio of Birger Sandzen in Lindsborg, Kansas. The objective of the group was “to further the interest of both artists and laymen in printmaking and collecting.”
Keywords: Prairie; print; makers; type; setting; printing; printer; Birger Sandzen; Lindsborg; art; artist; engraving; etcher; etching; medium; midwest; Kansas; life; lithograph; drypoints; aquatints; wood engraving; Eld Dorado; Coutts Museum